New highlights in cancer and depression multimorbidity: a scoping systematic review - Tang, Lin; Li, Danyang; Wu, Minghua (Frontiers in Oncology, 2025)
IntroductionThe co-occurrence of cancer and depression represents a prevalent and clinically significant form of multimorbidity, associated with poorer prognosis and increased healthcare burden. Despite this, current care models often operate in silos, resulting in fragmented management between oncology and psychiatry. This scoping review systematically maps existing evidence on cancer–depression multimorbidity to clarify epidemiological associations, elucidate underlying pathophysiological mechanisms, and synthesize integrated management strategies.MethodsThe review followed the Joanna Briggs Institute methodology for scoping reviews and adhered to the PRISMA-ScR reporting guidelines. A systematic search was conducted across four electronic databases (PubMed, Scopus, Web of Science, and Embase) for studies published between 2020 and 2025. Eligible studies included adult populations with cancer–depression multimorbidity, addressing epidemiology, mechanisms, or management outcomes.ResultsFrom 11,803 initial records, 36 studies met the inclusion criteria. The evidence consistently indicates a significant association between depression and increased risk of both all-cause and cancer-specific mortality across multiple cancer types. The included studies demonstrated notable heterogeneity in depression assessment methods and a geographical concentration in Asia, Europe, and North America.DiscussionThis scoping review establishes a substantial and consistent body of evidence linking depression to elevated mortality risk in patients with cancer, identifying depression as a critical and modifiable prognostic factor. The synthesis highlights key evidence gaps, including the underrepresentation of low- and middle-income countries and variability in depression measurement. These findings emphasize the need for systematic integration of depression screening and management into routine oncologic care and call for future research to develop standardized assessment tools and culturally adapted intervention models.